The Eleven Stages of University: How to Implement A Combination of Gamification-Board game-Metaverse-AI - Gamayanto, Indra; Sundjaja, Arta Moro; Mailangkay, Adele B L; Sirait, Tamsir Hasudungan (Teknik Informatika Universitas Suryakancana Cianjur, 2024)
AbstractTechnology is developing rapidly, and we need significant changes. One of them is the University. Universities are one of the pillars of the Country's progress, but not only this, the most basic level of education, from elementary school to higher levels, requires change. If we do not change and open our minds and eyes to change, we will not be able to deal with this long-term. Therefore, this concept research was done, and one of the most important reasons is